Osteophytic Iliac Venous Compression: Technical Considerations for a Bony May-Thurner Syndrome Variant - Shin, David S.; Mokkarala, Mahati; Allison, Stephen; Monroe, Eric J. (Journal of Clinical Interventional Radiology ISVIR, 2018)
May-Thurner syndrome (MTS) results in compression of the left common iliac vein between the spine and right common iliac artery leading to symptomatic venous outflow obstruction. The authors depict a classic case of MTS followed by four variant cases in which the primary culprit lesions causing compression were degenerative vertebral osteophytes. The osteophytic variant of MTS poses distinct diagnostic and therapeutic challenges.
Keywords: May-Thurner syndrome; venous compression; osteophyte; thrombolysis; stent